The impact of the appeal against the decisions of the Jordanian Chief Execution Officer in accordance with the Jordanian Execution Law No. 25 of 2007 - Al jarah, Misha‘al; Ghazawi, Mohamed Fahmy (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aims to identify the effect of the appeal against the decisions of the chief executive officer under the Jordanian execution law No. 25 of 2017. The researchers come up with the findings of this study which is to suspension of execution. This suspension is temporary till the appeal court takes its decision thereof. In addition, the findings confirm that the decision of the chief executive officer is made correctly and the appeal is only to temporary disrupt the execution due to the appeal does not affect the substantive right of convicted party or his right in enforcing the decision front of the execution authority when he/she refuse the appeal. The study aims to identify the conditions of appeal against the decisions of the Jordanian Chief of Execution. The researchers reached to the point of that the mere challenge of the decision before the Court of Appeal does not stop the execution and even the suspension of execution must be fulfilled. In addition, the request from the Chief Executive to suspend execution and a decision by the Chief Executioner to suspend implementation pending a decision by the Court of Appeal against the decision, either the decision is rescinded or the appeal is dismissed. The study also aims to determine the decisions of the Chief of execution that shall be challenged. The appeal includes all the decisions issued by the Chief Execution Officer in accordance with the Jordanian Execution Law No. (25) of 2007, as these are judicial decisions that appeal to the Court of Appeal.